2020
DOI: 10.1111/nph.16738
|View full text |Cite
|
Sign up to set email alerts
|

Different levels of energetic coupling between photosynthesis and respiration do not determine the occurrence of adaptive responses of Symbiodiniaceae to global warming

Abstract: Disentangling the metabolic functioning of corals' endosymbionts (Symbiodiniaceae) is relevant to understanding the response of coral reefs to warming oceans. In this work, we first question whether there is an energetic coupling between photosynthesis and respiration in Symbiodiniaceae (Symbiodinium, Durusdinium and Effrenium), and second, how different levels of energetic coupling will affect their adaptive responses to global warming. Coupling between photosynthesis and respiration was established by determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 93 publications
1
15
0
Order By: Relevance
“…66 ). The capacity of the AOX pathway measured in S. pistillata was 24% of Rd and is in the range as values previously reported for different species of Symbiodiniaceae grown in culture 20,65 . The observed lack of effect of the AOX inhibitor (i.e.…”
Section: Discussionsupporting
confidence: 86%
“…66 ). The capacity of the AOX pathway measured in S. pistillata was 24% of Rd and is in the range as values previously reported for different species of Symbiodiniaceae grown in culture 20,65 . The observed lack of effect of the AOX inhibitor (i.e.…”
Section: Discussionsupporting
confidence: 86%
“…This phenomenon could be explained by a relatively higher proportion of "light-418 dependent O2 consumption" through processes such as photorespiration and chlororespiration 419 that can serve as photoprotective electron sinks to dissipate excess excitation energy (Hughes et al 2018). Such a photosynthetic strategy has been observed for Symbiodiniaceae taxa that are inherently more tolerant of heat and/or light stress (Suggett et al 2008;Roberty et al 2014, Pierangelini et al 2020). This strategy is conducive to a higher overall PSII electron flow (Gorbunov et al 2011), yet would result in a smaller proportion of electrons that flow linearly to Ci fixation (Cardol et al 2011).…”
Section: Reliance Of Mangrove P Acuta On Photochemical Quenchingmentioning
confidence: 99%
“…CCMP827 lost 50% of its initial pigment content at 34 • C (Takahashi et al, 2013), but Symbiodinium sp. (Avir) tolerated a wide range (10-35 • C) of temperatures (Pierangelini et al, 2020). These results indicated that Symbiodiniaceae taxa exhibited different photobleaching threshold temperatures, which caused a dramatic loss of photosynthetic pigments and/or plastid photobleaching.…”
Section: Photobleaching Of E Voratum Scs01 Cells Under Thermal Stressmentioning
confidence: 80%